Policy mapping for establishing a national emergency health policy for Nigeria - Aliyu, Zakari Y (BioMed Central, 2002)
BACKGROUND: The number of potential life years lost due to accidents and injuries though poorly studied has resulted in tremendous economic and social loss to Nigeria. Numerous socio-cultural, economic and political factors including the current epidemic of ethnic and religious conflicts act in concert in predisposing to and enabling the ongoing catastrophe of accident and injuries in Nigeria. METHODS: Using the "policymaker", Microsoft-Windows(®) based software, the information generated on accidents and injuries and emergency health care in Nigeria from literature review, content analysis of relevant documents, expert interviewing and consensus opinion, a model National Emergency Health Policy was designed and analyzed. A major point of analysis for the policy is the current political feasibility of the policy including its opportunities and obstacles in the country. RESULTS: A model National Emergency Health Policy with policy goals, objectives, programs and evaluation benchmarks was generated. Critical analyses of potential policy problems, associated multiple players, diverging interests and implementation guidelines were developed. CONCLUSIONS: "Political health modeling" a term proposed here would be invaluable to policy makers and scholars in developing countries in assessing the political feasibility of policy managing. Political modeling applied to the development of a NEHP in Nigeria would empower policy makers and the policy making process and would ensure a sustainable emergency health policy in Nigeria.